Occupational Respiratory Exposure to Platinum Group Metals: A Review and Recommendations - Linde, Stephanus J L; Franken, Anja; du Plessis, Johannes L (Chemical research in toxicology, 2017)
Platinum group metals (PGMs) is a group of metals that include platinum, palladium, rhodium, ruthenium, iridium, and osmium. Occupational respiratory exposure to platinum has been reported since 1945, but studies investigating occupational exposure to palladium, rhodium, ruthenium, iridium, and osmium are scarce. This review provides a summation of the information available on the respiratory exposure to PGMs in various industrial settings, methods used to assess exposure, and the possible adverse health effects resulting from occupational exposure to PGMs. Of these effects, respiratory sensitization caused by soluble PGMs is of most importance. Metallic PGMs have not been shown to cause allergic reactions. This review reiterates that occupational respiratory exposure to PGMs is dependent on the type of industry where exposure takes place, the chemical form (soluble or insoluble) of the PGMs present in the workplace air, and the tasks performed by workers in the specific work areas. Sensitization to soluble platinum is associated with the degree of exposure to soluble platinum compounds, and the highest concentrations of soluble PGMs in workplace air have been reported for precious metals refineries where personal exposures frequently exceed the occupational exposure limit for soluble platinum (2 μg/m ). Additionally, this review emphasizes that personal exposure monitoring is preferred over area monitoring when assessing workers' exposure to PGMs. The legislation applicable to occupational exposure to PGMs is also discussed, and it is highlighted that the occupational exposure limit for soluble platinum has remained unchanged, in most countries, since 1970 and that too few countries have classified PGM compounds as respiratory or skin sensitizers. Finally, recommendations are made to ensure that future investigations are comparable in terms of the type of exposure monitoring (personal or area) conducted, the type of tasks included in the exposure monitoring program, and the format in which results are reported.